Childhood atopic dermatitis is associated with a decreased chance of completing education later in life: a register‐based cohort study. (7th June 2021) - Pálsson, K.; Slagor, R.M.; Flachs, E.M.; Nørreslet, L.B.; Agner, T.; Ebbehøj, N.E.
Abstract: Background: Atopic dermatitis (AD) has far‐reaching consequences in childhood and later in working life, but information on how it affects completion of education is sparse. Objectives: To compare the educational achievement of individuals with AD in childhood/adolescence and individuals without a history of AD. Methods: The study population included patients diagnosed with AD prior to the age of 16 registered in the Danish National Patient Register (DNPR) born in the period 1977–1993 and a 23‐fold matched control group from the background population. Cross‐linkage of five different Danish registers from 1977 to 2015 allowed comparison of AD patients with controls regarding completion of education. Results: In total, 10 173 individuals were registered with AD in the DNPR, while 234 683 individuals served as control group. Mild/moderate AD was associated with a decreased chance of completing basic compulsory education [hazard ratios (HR): 0.92, 95% CI: 0.90–0.95] and further academic education (HR: 0.96, 95% CI: 0.93–0.98). Severe AD was associated with a decreased chance of completing further academic education (HR: 0.86, 95% CI: 0.80–0.92), further vocational education (HR: 0.90, 95% CI: 0.84–0.97) and higher education: master's level (HR: 0.66, 95% CI: 0.53–0.81). Conclusion: Atopic dermatitis in childhood/adolescence is associated with a decreased chance of completing an education. Abstract : Linked Commentary: M. Möhrenschlager. J Eur Acad Dermatol Venereol 2021; 35 : 1746. https://doi.org/10.1111/jdv.17518 .